INFLUENCE OF POTENTIAL GENE POLYMORPHISMS ON PROPOFOL DOSAGE REGIMEN IN PATIENTS UNDERGOING ABDOMINAL HYSTERECTOMY - Ivanov, Emilija; Sterjev, Zoran; Budic, Ivana; Nojkov, Jordan; Karadjova, Dafina; Sivevski, Atanas (Macedonian Academy of Sciences and Arts, 2021)
Propofol (2,6-diisopropylphenol) is the most common intravenous anesthetic used in modern medicine. It is postulated that individual differences in genetic factors [polymorphism of single nucleotide polymorphisms (SNPs)] in the genes encoding metabolic enzymes, molecular targets and molecular binding sites of propofol can be responsible for susceptibility to propofol effects. The aim of our study was to investigate the influence of the cytochrome P450 2B6 isozyme CYP2B6 (rs3745274), γ-aminobutyric acid type A (GABAA) receptor α1 subunit GABRA1 (rs2279020) and ATP-binding cassette subfamily B member 1 ABCB1 (rs1045642) gene polymorphisms on propofol therapeutic outcomes in the patients undergoing abdominal hysterectomy. Ninety patients aged 29-74 years, with different ethnicities were included in this study. The presence of polymorphisms was analyzed using TaqMan SNP genotype analysis on Stratagene MxPro 3005P real-time polymerase chain reaction (qPCR). The distribution of all three genetic variants was within the Hardy-Weinberg equilibrium. There was no significant difference (p >0.05) in the allelic frequencies of polymorphic variants and genotype distributions between adult and older patients and between patients of different ethnicities. Our study did not detect a statistically significant influence of the CYP2B6 (c.516G>A), GABRA1 (c.1059+15G>A) and ABCB1 (c.3435T>C) variants on the variability of clinical parameters (doses for induction in anesthesia, additional doses, induction time and wake time after anesthesia and side effects of propofol). However, the observed trend on the possible influence of the CYP2B6 (c.516G>A) and GABRA1 (c.1059+15G>A) variants warrant an extension of these studies on a larger number of patients.
Keywords: ABCB1 gene; CYP2B6 gene; GABRA1 gene; Pharmacogenetic; Propofol